ANALISIS KESULITAN SISWA SMP DALAM MENYATAKAN PERISTIWA SEHARI-HARI DAN MENURUNKAN RUMUS LUAS BANGUN DATAR SEGIEMPAT - Maria Goreti Nina; Merlin Uru Endu (IKIP Siliwangi, 2019)
The purpose of this study was to find out how the mathematical communication skills of students in solving the problem of flat building of class VII triangles in one of the SMP in the city of Cimahi. Data collection uses written tests for 33 students. The research method used is descriptive qualitative research that is analyzing students' difficulties in solving mathematical communication skills on indicators stating everyday events and lowering the quadrangular flat building area formula of grade VII students of junior high school. The results of this study can be concluded that there are 6.06% (2 students) who have excellent mathematical communication skills, 93.94% (33 students) have good mathematical communication skills and 0% (no students) who have communication skills mathematically is not good at problem 1 which indicator states everyday events and decreases the formula of quadrilateral flat building. This is due to the lack of ability of students to communicate their ideas so that they cannot solve problems in the given questions and even if asked they can only smile and be quiet.